Programming teaching tools and the gender gap in the Information Technology field - Braga, Camille; Mochetti, Karina (Anais do Workshop de Informática na Escola (WIE); 2018: Anais do XXIV Workshop de Informática na EscolaDO - 10.5753/cbie.wie.2018.70, 2018)
The lack of participation of women in Information Technology is a worrying fact since diversity in any environment is vital for its evolution, especially in a field in which the role of users is changing and they have passed from consumers to producers. This study aims to analyze the reaction of boys and girls to an educational tool for teaching the basics of computer programming and computational thinking.